DISEASES THAT OCCUR IN THE HUMAN BODY AS A RESULT OF IMPROPER NUTRITION - Giyosova Sadokat Norovna (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Abstract: Malnutrition is one of the current global problems. Due to improper nutrition, millions of people in the world suffer from diseases related to the digestive system and die as a result. A number of scientific researches related to this diet are being carried out and applied to life by scientists of the world. Among these, one of the main ways is to involve the population in regular sports.